A surfactant free preparation of ultradispersed surface-clean Pt catalyst with highly stable electrocatalytic performance. (February 2018) - Tao, Lu; Zhao, Yueping; Zhao, Yufeng; Huang, Shifei; Yang, Yunxia; Tong, Qi; Gao, Faming
Abstract: High efficiency platinum-based catalyst demands the ultrafine size and well dispersion of Pt nanoparticles (NPs), with clean surface and strong interactions between the supports. In this work, we demonstrate a simple strategy for the preparation of ultra-dispersed surface-clean Pt catalyst with high stability, in which the Pt nanoparticles (NPs) with 1.8 ± 0.6 nm in size are anchored tightly on a 3D hierarchical porous graphitized carbon (3D-HPG) through galvanic replacement reaction. The as-obtained catalyst can undergo 2000 voltage cycles with negligible activity decay and no apparent structure and size changes for MOR during the durability test, and its mass activity for ORR only reduce 18.3% after 5000 cycles. The excellent performance is attributed to strong anchoring effect between carbon support and Pt nanoparticles. Graphical abstract: Highlights: A green strategy to prepare ultradispersed surface-clean Pt NPs is demonstrated. Pt NP/HPG shows excellent electrocatalytic performance for both ORR and MOR. Pt NP/HPG presents high endurance during the durability test.